Analisis Sembilan Langkah Pembangunan Pendidikan Jawa Barat Menuju Terwujudnya Gapura Panca Waluya Prespektif Hukum Administrasi Negara Dan Fiqih Siyasah - Nursetiawati Nursetiawati; Jefik Zulfikar Hafizd; Ilham Bustomi; Abdul Fatakh (Equality : Jurnal Hukum dan Keadilan, 2026)
This study analyzes the Governor of West Java Circular Letter Number 43/PK.03.04/KESRA of 2025 concerning the Nine Steps of Educational Development toward Gapura Panca Waluya from the perspectives of State Administrative Law and fiqh siyasah. The study is based on issues related to educational costs, weak character formation, and the need for regional policies that are responsive to the practical needs of educational institutions. This research employed a qualitative method with a case study approach at SMAN 1 Sumber, Cirebon Regency. Primary data were collected through observation, semi-structured interviews, and documentation, while secondary data were obtained from laws and regulations, the circular letter, books, and scholarly journals. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings show that the circular letter functions as an administrative policy instrument that is administratively valid but normatively limited. At the school level, the policy is fairly effective in directing character building, discipline, healthy habits, and controlling school activities that burden parents. From the perspective of fiqh siyasah, the policy is consistent with the principles of justice, public benefit, equality, proportional freedom, and deliberation at the implementation stage. This study concludes that the circular letter can serve as an effective administrative guideline, although stronger formal regulatory support is still needed to ensure more optimal and sustainable implementation.